Biological Effects of Leptospiral Lipids - Stalheim, O. H. V. (1968)
Lipids were extracted from virulent Leptospira pomona and were purified. These lipids fixed complement in the presence of antiserum to L. pomona but did not stimulate the production of homologous agglutinins in rabbits, mice, or hamsters. When subsequently challenged, all of the mice and hamsters were fully susceptible to L. pomona. The lipid material was neither dermonecrotic nor lethal for mice or hamsters, but 382 μg of lipid from virulent or avirulent leptospires inhibited the growth of normal mice. Leptospiral lipids were toxic for peritoneal macrophages maintained in vitro, and when administered simultaneously with a million lethal doses of L. pomona, the lipids hastened death of the hamsters, presumably by inhibiting phagocytosis early in the course of the infection.